2011
DOI: 10.1007/s13280-011-0167-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Biological and Environmental Phenology at a Landscape Level from 30 Years of Fixed-Date Repeat Photography in Northern Sweden

Abstract: A 30-year series of photographic records were analysed to determine changes in lake ice cover, local (low elevation) and montane (high elevation) snow cover and phenological stages of mountain birch (Betula pubescens ssp. czerepanovii) at the Abisko Scientific Research Station, Sweden. In most cases, the photographic-derived data showed no significant difference in phenophase score from manually observed field records from the same period, demonstrating the accuracy and potential of using weekly repeat photog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
(40 reference statements)
3
11
1
Order By: Relevance
“…Stewart et al, 2005;Åkerman and Johansson, 2008;Andrews et al, 2011;Callaghan et al, 2013). Our results for trends in snowmelt onset are consistent with findings from other studies, which observed an earlier onset of snowmelt in North America, northern Europe and the Alps (e.g.…”
Section: Tablesupporting
confidence: 92%
“…Stewart et al, 2005;Åkerman and Johansson, 2008;Andrews et al, 2011;Callaghan et al, 2013). Our results for trends in snowmelt onset are consistent with findings from other studies, which observed an earlier onset of snowmelt in North America, northern Europe and the Alps (e.g.…”
Section: Tablesupporting
confidence: 92%
“…At the Eurasian scale, a significant trend toward later dates in the onset date of the first snow cover, and a declining trend of the end date of snow cover has been reported (Peng et al 2013). Trends toward later first snowfall and/or earlier snowmelt have been observed e.g., over most of the Russia ) and in northern Sweden (Andrews et al 2011). Our results showed no significant change in the ending date of the snow cover.…”
Section: Cold Season Changes In the Värriötunturit Fell Areacontrasting
confidence: 39%
“…(ii) using conservation to offset carbon emissions. -Monitoring (i) there is a need to develop standardized protocols for integrated and adaptive long-term monitoring [168] so that meta-analyses can be performed and a new generation of monitoring [169,170] can target the success and/or failures of adaptation measures implemented in the future.…”
Section: Discussionmentioning
confidence: 99%